Epithelial-to-Mesenchymal Transition in the Female Reproductive Tract: From Normal Functioning to Disease Pathology - Bilyk, Olena; Coatham, Mackenzie; Jewer, Michael; Postovit, Lynne-Marie (Frontiers in Oncology, 2017)
Epithelial-to-Mesenchymal transition (EMT) is a physiological process that is vital throughout the human lifespan. In addition to contributing to the development of various tissues within the growing embryo, EMT is also responsible for wound healing and tissue regeneration later in adulthood. In this review, we highlight the importance of EMT in the development and normal functioning of the female reproductive organs (the ovaries and the uterus) and describe how dysregulation of EMT can lead to pathological conditions such as endometriosis, adenomyosis and carcinogenesis. We also summarize the current literature relating to EMT in the context of ovarian and endometrial carcinomas, with a particular focus on how molecular mechanisms and the tumor microenvironment can govern cancer cell plasticity, therapy resistance and metastasis.